Supporting pentatomic organizations using DNA architectural constructs - John P. T. Mo; Sekhar Chattophdhyay (The International Journal of Management Science and Information Technology (IJMSIT), 2012)
The volatility and fierce competition of the business environment in the 21st century has forced enterprises to constantly review and change their structure, hierarchy, command, control and management styles. The pentatomic organization enterprise architecture offers a non-conventional approach to address these challenges. The pentatomic framework integrates five different enterprise models and adds a feedback loop to enable dynamical adaptation of enterprise architecture to changing business requirements. The dynamism and expandability of pentatomic organizations require architectural constructs that are flexible and align with the fundamental principles. DNA constructs have evolved from the study of merger and acquisitions of enterprises. The new modelling approach is particularly adaptable to changes and enterprise re-engineering due to merger and acquisition. This paper explores the use of DNA modelling methodology to support the implementation of pentatomic organizations which might have gone through a series of changes. The outcome is a more efficient enterprise changing process that ensures a smooth transition of state of enterprise.
Keywords: 650; Enterprise Modelling; Enterprise Architectures; Pentatomic Organisations; DNA enterprise constructs; enterprise transformation; dynamic enterprises; change management; organisational integration